Implementation of Learning Cycle’s Model Based on SCL (Student-Centered Learning) to Improve Students’ Creative Thinking Ability in Learning Evaluation Subjects at Universitas Almuslim - Fatimah Fatimah; M. Taufiq (Indonesian Review of Physics (IRiP), 2021)
The main problems in conducting this research include 1) The ability of the students to analyze the question was less creative in answering; 2) the students learning activities were still low; 3) the students’ interest and response were still low in the instruction. Those problems that had an impact on the instruction were not a success as individual and classical. Therefore, we need an innovative instruction model in enhancing the learning and teaching process, such as; SCL-based Learning Cycle model. This research was Classroom Action Research (CAR) which consisted of planning, acting, observing, and reflecting. This research was the students in the fifth semester in the Physics Education Department that consisted of 21 students. Based on the research results, it was concluded that the implementation of Learning Cycle 5E through SCL-based had improved students’ creative thinking skills, lecturer’s and students’ activities in the teaching and learning process.